Perilaku Oportunistik Creative Accounting dan Upaya Menginternalisasi Nilai Etika; Suatu Kajian Psikologi - Ali, Iqbal M. Aris (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2010)
Conflict analysis as described in agency theory shows that asymetric information could occur. Information given to the principal might be sorted out in order to secure agentsâ interests. This behavior is called oportunisitic behavior that encourages the practice of earnings management. To predict and explain opportunistic behavior, Watts and Zimmerman formulate three hypotheses: (1) bonus plan hypotheses, (2) debt covenant hypotheses, and (3) the political cost hypotheses. Research results based on these hypotheses prove that the practice of earnings management is more likely to be done without regard to principles of ethical values. By using cognitive and humanistic psychology, such as the Theory of Reasoned Action (TRA), and the Theory of Planned Behavior (TPB)) the motive for opportunistic behavior could be explained and ethical behaviour that are influenced by social norms such as religions could be reconstructed. If individual feels that opportunistic behavior is contrary to religious norms and rules (GAAP /PSAK) then he will refuse to behave opportunistically. The rules of accounting policies that provide the opportunity for agents to select based on merit, enable rationalization of the opportunistic behavior as a self reaction mechanism that could justify the behavior as efforts to protect from external threats.